PENINGKATAN KEMAMPUAN GURU-GURU SENI BUDAYA DALAM PEMBELAJARAN SENI RUPA DI SMPN BUKITTINGGI - San Ahdi San Ahdi; Wisdiarman Wisdiarman; Suib Awrus; Erwin A (Jurusan Seni Rupa, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2019)
The main problem experienced by art and culture teachers at bukittinggi junior high school is not being able to carry out fine arts learning, so that it has an impact on the achievement of students' art learning outcomes. This is caused by several factors, including; 1) in general, the art and culture teachers of Bukittinggi Public Middle School have not mastered art material, even though fine art is one of the subjects of art and culture and must be taught from class VII to class IX. 2) in general (80%) arts and culture teachers had dance and music drama education backgrounds and only 20% had art education backgrounds. 3) in general the art and culture teachers at bukittinggi junior high school have not mastered the art learning strategy. These problems need to be solved by providing training activities on art materials and learning strategies for arts and culture teachers. The aim is that teachers can master the fine arts material and learning strategies well. The results of this activity are 1) 86.84%) teachers have mastered fine art (batik) material both theory and practice, well, 2) 89.47 %% of teachers have mastered fine art learning strategies. Thus it can be concluded, that in general the art and culture teachers at bukittinggi junior high school have been able to master fine arts material and fine arts learning strategies, so that it is expected to be able to be applied in art learning in schools.